2019
DOI: 10.9734/ajrid/2019/v2i130096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Susceptibility Pattern of Escherichia coli and Salmonella spp Isolated from Diarrhoeic Children in Selected Health Centres in Sokoto, Nigeria

Abstract: Aim: To determine the prevalence and antibiotic susceptibility patterns of E. coli and Salmonella spp. associated with childhood diarrhoea in our locality. Study Design: Cross-sectional study. Place and Duration of Study: School of Medical Laboratory Science, Usmanu Danfodiyo University, Sokoto between May and October 2017. Methodology: A total of 236 faecal samples were collected from children less than or equal to five years and were processed, isolates were identified following standard ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The resistance to Ciprofloxacin is comparable to the study of Malik et al (2021) that reported resistance rate of 73.6% to Ciprofloxacin. However lower resistance rate of 24.5% and 17.8% to Ciprofloxacin was reported by Ya'aba et al (2020) and Najim et al (2019). Resistance to Nalidixic acid is comparable to results of Sharma et al (2013) and Wagle et al (2018) who reported resistance rates of 78.9% and 71.5% respectively.…”
Section: Multiple Antibiotic Resistance Index (Mari) Of Escherichia C...supporting
confidence: 67%
See 2 more Smart Citations
“…The resistance to Ciprofloxacin is comparable to the study of Malik et al (2021) that reported resistance rate of 73.6% to Ciprofloxacin. However lower resistance rate of 24.5% and 17.8% to Ciprofloxacin was reported by Ya'aba et al (2020) and Najim et al (2019). Resistance to Nalidixic acid is comparable to results of Sharma et al (2013) and Wagle et al (2018) who reported resistance rates of 78.9% and 71.5% respectively.…”
Section: Multiple Antibiotic Resistance Index (Mari) Of Escherichia C...supporting
confidence: 67%
“…This is in contrast to various other studies where higher resistance rate was recorded. Engda et al (2018) and Najim et al (2019) reported that E. coli isolates were totally resistant (100%) to amoxicillin-clavulanic acid while Ya'aba et al (2020) and Malik et al (2021) reported resistance level of 61.22% and 81.1% to amoxicillin-clavulanic acid respectively. Lower resistance rate to Amoxicillin/clavulanic acid observed in this study could be due to the effectiveness of the drug combinations.…”
Section: Multiple Antibiotic Resistance Index (Mari) Of Escherichia C...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Sokoto Nigeria 24 shows 5.9% of salmonella species were isolated among those were having 100% sensitivity to ofloxacin, ciprofloxacin and ceftriaxone while no sensitivity was noted towards ampicillin and augmentin.…”
Section: Discussionmentioning
confidence: 99%